2015
DOI: 10.3171/2014.12.jns141218
|View full text |Cite
|
Sign up to set email alerts
|

Role of superior hypophyseal artery in visual function impairment after paraclinoid carotid artery aneurysm surgery

Abstract: A ccording to the related branching artery or anatomical relationships, there are many classifications of intradural proximal carotid artery aneurysms. In the literature, the term "paraclinoid carotid aneurysm" is often used because it includes all carotid artery aneurysms originating from the internal carotid artery (ICA) between the distal dural ring and the origin of the posterior communicating artery. 11,12,21 The superior hypophyseal artery (SHA) is well known as a branching artery of paraclinoid carotid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 23 publications
(47 reference statements)
1
6
0
Order By: Relevance
“…Hence, it might be safe to disconnect the SHA on one side in a high percentage of cases. This hypothesis is consistent with the results of a large series of studies by Horiuchi et al on the visual outcomes of clipped SHA aneurysms 31 . Two of our patients had blood vessels from the SHA involved in blood supply to the tumor.…”
Section: Discussionsupporting
confidence: 93%
“…Hence, it might be safe to disconnect the SHA on one side in a high percentage of cases. This hypothesis is consistent with the results of a large series of studies by Horiuchi et al on the visual outcomes of clipped SHA aneurysms 31 . Two of our patients had blood vessels from the SHA involved in blood supply to the tumor.…”
Section: Discussionsupporting
confidence: 93%
“…Johnson et al ( 21 ) stated that homonymous hemianopsia developed after the operation in a patient who underwent SHA aneurysm embolization. Horiuchi et al ( 22 ) stated that a visual deficit of 13% was observed in a series of 70 patients with SHA aneurysms, and it was commented that unilateral sacrification could not always be performed in SHA aneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…7 A homonymous hemianopia was reported after the SHA was occluded during aneurysm em-bolization with Onyx HD-500. 15 Horiuchi et al conducted a large series on visual outcome after clipping an SHA aneurysm; 14 the overall incidence of a visual deficit was 13%, among which 1 of 18 cases experienced visual loss despite SHA preservation, 2 of 22 cases had visual loss after sacrifice of the SHA, and 6 of 20 cases endured visual deficit with an undetermined condition of the SHA. In their series, however, the authors excluded carotid cave aneurysms, an area in which two-thirds of pSHAs originate, and data did not specify whether the SHAs were primary or secondary.…”
Section: Discussionmentioning
confidence: 99%